Kierkegaard as Psychologist - McCarthy, Vincent (Northwestern University Press, 2015)
Kierkegaard's psychological thought has always been acknowledged as very rich-Reinhold Niebuhr hailed him as the greatest psychologist of the soul since Augustine-and has had a major influence on Heidegger, Sartre, and existential psychoanalysis. Nevertheless, his accomplishment has not always been fully appreciated, in part because it is so scattered across his works. As Vincent McCarthy demonstrates in Kierkegaard as Psychologist, Kierkegaard was pursuing "psychology" before there was a formally recognized academic field bearing that name, and a coherent thread runs through the so-called pseudonymous works. McCarthy elucidates often-difficult texts, highlights the rich psychological dimension of Kierkegaard's thought, and provides an introduction for the nonspecialist and a commentary on Kierkegaard's psychology that will interest both specialists and nonspecialists, while engaging in rich comparisons with such figures as Freud and Heidegger.